Determinação de bussulfano em plasma através de cromatografia líquida de alta eficiência com detector de arranjo de diodos e derivatização com dietilditiocarbamato de sódio - Charline Fernanda Backes; Sandrine Comparsi Wagner; Fernando Dal Pont Morisso; Marina Venzon Antunes; Rafael Linden; Marcelo Capra (Química Nova, 2012)
A high performance liquid chromatographic-diode array detection method for the determination of busulfan in plasma was developed and validated. Sample preparation consisted of protein precipitation followed by derivatization with sodium diethyldithiocarbamate and liquid-liquid extraction with methyl-tert-butyl ether. Chromatograms were monitored at 277 nm. Separation was carried out on a Lichrospher RP 18 column (5 µm, 250 x 4 mm). The mobile phase consisted of water and acetonitrile (20:80, v/v). The method presented adequate specificity, linearity, precision and accuracy and allowed reliable determination of busulfan in clinical plasma samples, being applied to three patients submitted to bone marrow transplantation.